Agricultural mosaics offer nesting habitat to dabbling ducks in the arid Intermountain West of the United States - Casey M. Setash; Adam C. Behney; James H. Gammonley; Liba Pejchar; Matt A. Reddy; David N. Koons (Ecosphere)
Abstract The debate over the best agricultural practices for biological conservation often focuses on the degree to which agricultural lands should be interspersed with desirable habitat versus protecting lands entirely from production. It is important to understand the benefits agriculture provides for wildlife because it is consuming an increasing proportion of the landscape. We evaluated the nesting ecology of breeding ducks within a mosaic of flood‐irrigated conservation areas and agricultural lands in hay production. We assessed how habitat features at two spatial scales across these lands were related to nest site selection, nest density, and nest survival of multiple duck species. Birds selected nest sites with higher visual obstruction, a higher proportion of shrubs around the nest, and less bare ground, but we did not detect evidence of selection per se at larger spatial scales. Nest density was marginally higher along linear features, including irrigation ditches and riparian stretches, but nest survival remained similar across land‐use types and habitats features. This system is representative of many agricultural landscapes around the globe and highlights the ways agroecosystems can be managed to maintain habitat suitability for wildlife on working lands.